Reflections on Sundanese Sandekala: Legal Aspects and Environmental Awareness Post-Pandemic Covid-19 - Sarip, Sarip; Romdhoni, Ali; Kusuma Dewi, Elya; Syarifudin, Aip (Universitas Kuningan, 2025)
This study aims to examine the legal review of Sundanese local wisdom, specifically the concept of Sandekala traditionally practiced by West Java community. The analysis evaluated the effect of government policies on the implementation of local wisdom values in the context of education, technology, and restrictions during the COVID-19 pandemic, with particular attention to the role in fostering environmental awareness post-pandemic. Moreover, this study examined how these policies complement or deviate from the legal principles underlying local wisdom and environmental sustainability. An analytical method was used to review legal journals and online discussions, investigating how shifts in the understanding and application of local wisdom values have occurred in response to government measures. Furthermore, there are also big myths about these values that cause problems for keeping local wisdom true and useful. The results showed the importance of matching government policies with local values, including Sandekala, as a form of customary law that remains relevant, and ensuring the continuity of inclusive cultural and legal practices while protecting the environment in the post-pandemic context. This study provides valuable insights into how policies can enhance local wisdom and ensure compliance with relevant legal frameworks. In conclusion, keeping local wisdom is not just culture but also part of sustainable and inclusive law in Indonesia. Local wisdom should be kept and studied using science and technology.